BAL fluid cells in newly diagnosed pulmonary sarcoidosis with different clinical activity - Danila, Edvardas (Informa Healthcare, 2009)
BACKGROUND: Sarcoidosis is associated with an increase in the number of alveolar T cells (CD3(+) cells) and an increase of the CD3(+)CD4(+) lymphocyte subset. However, the number of lymphocytes and the CD4/CD8 ratio in bronchoalveolar lavage (BAL) fluid are highly variable in sarcoidosis. Comparative studies have demonstrated that geographic and ethnic factors are linked to the specific characteristics of patients with sarcoidosis. AIM OF THE STUDY: To investigate peculiarities of BAL fluid (BALF) cell patterns in different clinical activity of pulmonary sarcoidosis at the time of diagnosis. MATERIAL AND METHODS: A total of 308 non-treated patients (138 asymptomatic and 170 with sarcoidosis-related symptoms) and 40 previously empirically steroid-treated patients with newly diagnosed sarcoidosis have been prospectively examined. RESULTS: Significant BAL fluid lymphocytosis and increased CD4/CD8 ratio were characteristic for all three sarcoidosis patient groups. A total of 12% of asymptomatic patients, 3% of patients with sarcoidosis-related symptoms, and 5% of previously treated symptomatic patients had normal BALF cell counts. Non-treated patients with sarcoidosis-related symptoms had significantly higher lymphocytosis (45±19% versus 39±17%, P<0.01), CD4/CD8 ratio (9.3±5.0 versus 5.7±4.5, P<0.001), and total BALF cell count (411±322 106/mL versus 334±273 106/mL, P<0.05), compared with asymptomatic patients. However, previously treated symptomatic patients had lower lymphocytosis (39±15% versus 45±19%, P=0.058), and total BALF cell count (292±166 106/mL versus 411±322 106/mL, P<0.05) compared with non-treated symptomatic patients. The same trend was noticed for CD4/CD8 ratio (8.3±4.8), although a statistically significant difference was not achieved. CONCLUSIONS: Independently of clinical symptoms at the time of diagnosis sarcoid patients have significantly different BAL fluid cell patterns compared to healthy persons. BAL fluid cell changes are more prominent in corticosteroid non-treated patients with clinically active sarcoidosis. Treatment with systemic corticosteroids may modify typical BALF cellular patterns of sarcoidosis.